2007
DOI: 10.1007/s10571-007-9212-7
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Regulates the Viability and Differentiation of Rat Midbrain Neural Stem Cells

Abstract: (1) Neurogenesis driven by neural stem cells (NSCs) is regulated by physiological and pathological factors. Melatonin (MT) has profound neurotrophic and neuroprotective effects. Hence, we studied the role of MT in regulating the viability and differentiation of NSCs derived from rat ventral midbrain. (2) NSCs were isolated from the rat ventral midbrain. The viability of NSCs was determined by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-ulfophenyl)-2H-tetrazolium assay. The differentiation of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 18 publications
6
89
2
4
Order By: Relevance
“…The implication of melatonin agonist properties of agomelatine in this process is consistent with recent data showing a melatonin-induced increase of new granule cell maturation and survival in mice (Ramirez-Rodriguez et al, 2009). This neurotrophic role of melatonin was also suggested by in vitro data on viability and differentiation of neural stem cells (NSCs), which was associated to an increase in BDNF expression (Kong et al, 2008), even if in our experimental conditions melatonin alone does not modify cell survival. Indeed, we also found an increase in hippocampal BDNF level in agomelatine-and melatonin-treated rats, but for melatonin the increase is less pronounced.…”
Section: Adult Neurogenesis and Antidepressantsupporting
confidence: 80%
See 1 more Smart Citation
“…The implication of melatonin agonist properties of agomelatine in this process is consistent with recent data showing a melatonin-induced increase of new granule cell maturation and survival in mice (Ramirez-Rodriguez et al, 2009). This neurotrophic role of melatonin was also suggested by in vitro data on viability and differentiation of neural stem cells (NSCs), which was associated to an increase in BDNF expression (Kong et al, 2008), even if in our experimental conditions melatonin alone does not modify cell survival. Indeed, we also found an increase in hippocampal BDNF level in agomelatine-and melatonin-treated rats, but for melatonin the increase is less pronounced.…”
Section: Adult Neurogenesis and Antidepressantsupporting
confidence: 80%
“…These changes led to similar increases in newly formed neurons or astrocytes, as shown by the confocal microscopy analyses revealing no effect of agomelatine on the respective percentages of BrdU-NeuN-vs BrdU-GFAP-labeled cells neither in the DH nor in the VH (Table 1). As melatonin has been implicated in hippocampal cell survival (Kong et al, 2008;Quiros et al, 2008;Manda et al, 2009;Ramirez-Rodriguez et al, 2009), we tried to show a possible implication of melatonin agonist properties in the effect of agomelatine by adding a melatonin inhibitor together with agomelatine. We found that the daily pretreatment with the …”
Section: Agomelatine Increases Cell Survival In Vivomentioning
confidence: 99%
“…In addition, we observed that in melatonin-treated cell cultures, new neurons established contacts with surrounding cells and formed a network. Recently, another in vitro study has reported that 10 À6 mM melatonin modulated rat midbrain neural stem cells viability (Kong et al, 2008). Our data suggest that 10 À6 -10 À4 mM of melatonin caused a 28 and 26% increase in the number of surviving progenitor cells undergoing differentiationFpossibly through an antiapoptotic effect (Reiter, 1998b).…”
Section: à6mentioning
confidence: 48%
“…Melatonin has been previously found by others to enhance neurogenesis in vitro but no data on adult neural precursor cells from the hippocampus were available (Kong et al, 2008;Moriya et al, 2007). The published findings were difficult to extrapolate to adult neurogenesis because embryonic and adult neural stem cells have distinct properties, the details of which are poorly understood.…”
Section: Melatonin Promotes Neuronal Differentiation Of Precursor Celmentioning
confidence: 99%
See 1 more Smart Citation